On the issue of turkish-armenian relations' research - S M Matevosyan (Vestnik RUDN International Relations, 2009)
This article is concerning the main trends in Turkish and Armenian studies on Armenian-Turkish relations. The works of specialists cover Armenian-Turkish relations, starting from the period of Armenia independence and up to the present moment.